Transportation, Social Inequality and Spatial Capital: Comparative Analysis between Buenos Aires and Santiago de Chile - Ricardo Apaolaza; Jorge Blanco; Natalia Lerena; Ernesto López-Morales; Michael Lukas; Maite Rivera (Íconos)
This paper studies how the characteristics of Latin American urban transportation generate dimensions of dispute of ‘spatial capital’, meaning an individually internalizable type of urban resource which results from the combination of objective material conditions and subjective socio-cultural conditions. These conditions determine a socially differentiated use of territory and sometimes are decisive elements in opening new niches for high-end real-estate producers and consumers, hence linking with processes of displacement and exclusion. The study cases compare four neighborhoods from Buenos Aires and Santiago de Chile, two peripherals and two pericentrals. The results show, considering the role of new infrastructure, a strong difference between residents from the peripheral cases and little difference in the pericentral cases, identifying, however, processes of a dispute over the ownership and use of urban space and the neighborhood, in all the cases.